Response of a Zn(ii)-based metal–organic coordination polymer towards trivalent metal ions (Al3+, Fe3+ and Cr3+) probed by spectroscopic methods. Issue 21 (10th May 2021) - Daga, Pooja; Manna, Priyanka; Majee, Prakash; Singha, Debal Kanti; Hui, Sayani; Ghosh, Ananta Kumar; Mahata, Partha; Mondal, Sudip Kumar
Abstract : A Zn-based MOCP showed non-monotonous luminescence responses towards Al 3+, Cr 3+ and Fe 3+ due to complexation based on hard–hard acid–base interactions that resulted in increased rigidity for Al 3+ and LMCT using vacant d-orbitals of Cr 3+ and Fe 3+ . Abstract : A new zinc-based two-dimensional coordination polymer, [Zn(5-AIP)(Ald-4)]·H2 O (5-AIP = 5-amino isophthalate, Ald-4 = aldrithiol-4), 1, has been synthesized at room temperature by the layer diffusion technique. Single-crystal X-ray diffraction analysis of 1 showed a two-dimensional bilayer structure. An aqueous suspension of 1 upon excitation at 300 nm displayed an intense blue emission at 403 nm. The luminescence spectra were interestingly responsive and selective to Al 3+, Cr 3+ and Fe 3+ ions even in the presence of other interfering ions. The calculated detection limits for Al 3+, Cr 3+ and Fe 3+ were 0.35 μM (8.43 ppb), 0.46 μM (22.6 ppb) and 0.30 μM (15.85 ppb), respectively. Notably, with the cumulative addition of Al 3+ ions, the luminescence intensity at 403 nm decreased steadily with a gradual red shift up to 427 nm. Afterward, this red shifted peak showed a turn-on effect upon further addition of Al 3+ ions. On the other hand, for Cr 3+ and Fe 3+ ions, there was only drastic luminescence quenching and a large red shift up to 434 nm. This indicated the formation of a complex between 1 and these metal ions, which was also supported by the UV-Visible absorption spectra of 1 that showed the appearance of a new band at 280 nm in the presence of these three metal ions. The FTIR spectra revealed that these ions interacted with the carboxylate oxygen atom of 5-AIP and the nitrogen atom of the Ald-4 ligand in the structure. The luminescence lifetime decay analysis manifested that a charge-transfer type complex was formed between 1 and Cr 3+ and Fe 3+ ions that resulted in huge luminescence quenching due to the efficient charge transfer involving the vacant d-orbitals, whereas for Al 3+ ions having no vacant d-orbital, turn-on of luminescence occurred because of the increased rigidity of 1 upon complexation.